FAKTOR KOMUNIKASI DAN SUMBER DAYA DALAM IMPLEMENTASI KEBIJAKAN PERKREDITAN BANK MEGA SYARIAH PASAR FLAMBOYAN KOTA PONTIANAK - Rendy Nurhendratmoko E.21111113 (FISIP Universitas Tanjungpura, 2013)
Writing a journal is intended to reveal about the Implementation of Credit Policy Bank Mega Syariah Branch Flamboyan Market In Pontianak . Problems customers / credit pemimjam qualify or deserve credit , but the credit goes after these customers bermasalahan in installments or monthly installments , experienced penunggakkan it is quite interesting to study . Through research journal is intended to find out about credit bottlenecks in the implementation process of Bank Mega Syariah Branch Flamboyan Market in the city of Pontianak order in the customer 's credit is not a problem . Arrears . There are 3 things that affect the implementation process Credit Policy is : 1 . Communication , 2. Bureaucratic structure 3. resources. In the credit policy implementation in Bank Mega Syariah Mandiri application of communication , bureaucratic structure , disposition already optimally However , in practice this , the Bank Mega Syariah in Pontianak City also experienced a number of barriers in implementing lending at Bank Mega Syariah Mandiri . The obstacle is the presence of bad loans caused by a bank error or due to customer error . Keywords : Implementation of policy , Credit Institutions , Bank Syariah